How to negotiate anything with anyone anywhere around the world - Acuff, Frank L. (AMACOM/ American Management Association, 2008)
Are formal agendas required in Mexico? Is July a good time to schedule meetings with Norwegians? Here are the do's and don'ts of negotiating abroad!